Employing the aesthetics of Arabic letters in the artistic structure of commercial advertising (Journal of the College of Basic Education, 2024)
search Arabic characters and aesthetics in the commercial as a variable component of Arabic characters in appearance, shape, color and direction, and the semantics of those variables in form or design or configure the printed Declaration.The search included four chapters, the first chapter (methodological framework), the problem of searching and raised the following question: is it possible to recruit Arabic letters in technical architecture aesthetics for commercial? Then the importance of research, research objectives and limits the search and then select the most important terms and concepts. Chapter II (previous studies theoretical framework) was divided into two sections was the first researcher to study specialized beauty general concept of beauty in calligraphy, aesthetic uses of calligraphy in Arabic script, character uses in modern commercial advertising and finally structures The Biblical line, second topic which is devoted to study design systems used in the commercial and aesthetic underpinnings of the Declaration, the researcher out of a set of indicators arising from the conceptual framework adopted as tools to analyze a sample search 0 being worth mentioning